Bilateral Diffuse Uveal Melanocytic Proliferation Secondary to Rectal Adenocarcinoma: A Case Report and Literature Review - Tong, Nianting; Wang, Liangyu; Wang, Nan; Zhou, Zhanyu (Frontiers in Medicine, 2021)
Background: Bilateral diffuse uveal melanocytic proliferation (BDUMP) is a rare paraneoplastic intraocular syndrome that causes progressive visual loss in patients, and is associated with an underlying malignancy. Recently, the incidence of BDUMP has increased with the prolonged life expectancy of oncology patients. Case presentation: We report a case of a 68-year-old man with significant visual loss in both eyes. The patient presented with a diffusely thickened choroid and ciliary body, extremely shallow anterior chamber, increased intraocular pressure, and cataract formation, accompanied by exudative retinal detachment in both eyes. He underwent a pars plana vitrectomy and choroidal biopsy, which revealed benign proliferation of melanocytes. A small amount of subretinal fluid persisted, and uveal thickness persisted in the early postoperative period. During the 1-year follow-up assessment, he underwent rectal tumor resection, and was pathologically diagnosed with rectal adenocarcinoma. Six months after the rectal tumor resection, the subretinal fluid was completely absorbed and the retina had reattached. The thickness of both the ciliary body and choroid had significantly decreased. Conclusion: This case report describes a rare paraneoplastic intraocular syndrome, BDUMP, which was associated with rectal adenocarcinoma. Treatment for the primary malignancy gradually improved the visual symptoms and signs.